Dead air : the night that Orson Welles terrified America - Hazelgrove, William Elliott, 1959- (Rowman & Littlefield, 2024)
"On Halloween Eve 1938, Orson Welles put on a radio play of 'War of the Worlds' and terrorized an uneasy American public on the brink of World War II, perpetuating the greatest hoax in history and changing media forever. This book brings to life this fateful night and follows the life and career of Welles before and after the historic broadcast"--